Turning EPIC data into science products - Sutton, Marshall (Frontiers in Remote Sensing, 2025)
The EPIC (Earth Polychromatic Imaging Camera) onboard the DSCOVR mission takes full disc illuminated pictures of the earth in 10 spectral bands, ranging from infrared to ultraviolet. Scientists use the data from EPIC to study the surface and atmosphere of the earth, including aerosols, ozone, volcanic plumes, vegetation, and the ocean. This paper describes how raw data from the EPIC instrument is turned into level-2 science products. It describes the hardware and processes that go in to creating a data pipeline for disseminating these science products to the wider community.